Silica supported polyaminals for selective CO2 capture. (2021) - Senthilkumaran, M.; Saravanan, C.; Puthiaraj, P.; Muthu Mareeswaran, P.
Abstract: Nitrogen containing mesoporous polymers and amine functionalized mesoporous silica are promising candidates for CO2 capture application. Here, we have synthesized nitrogen rich polymer (polyaminals) with silica support. The one-pot poly condensation reaction is used to achieve the target material without using catalyst. The nature of bond and structure of the prepared polymers are confirmed using FT-IR and 13 C CP-MAS NMR techniques. The amorphous nature of these polymers are examined by powder XRD. The surface morphology of Si-PAs is characterized by SEM analysis. The textural properties of the materials are studied by N2 sorption isotherms at 77 K.